(untitled) (Global Journal of Human-Social Science, 2025)
Annotation-This article is devoted to the creation, activity and revival of scouting in Russia. Using the example of the Smolensk region, the authors consider the creation of a scout society, show the goals and objectives, the structure of the organization, the charter and documentation. The authors of the work introduce into scientific circulation archival materials from the funds of the State Archives of the Smolensk Region